Optimizing the trauma resuscitation bay during the covid-19 pandemic - Stephanie Bonne; David Hugh Livingston; Catherin Morello; Adam Fox (Trauma Surgery & Acute Care Open)
The covid-19 global pandemic due to the SARS-CoV2 (CoV2) virus has created the need to adapt hospital workspaces and staffing models, and trauma is no exception. While the optimal configuration of a trauma resuscitation area is debatable, the space needs to be large enough to accommodate the trauma team and ancillary staff. It also needs to have ready access to supplies and equipment to quickly and easily control hemorrhage, secure an airway and initiate fluid resuscitation. Lastly, stores of personal protective equipment in the form of fluid resistant gowns, head covering, face shield, and gloves (both sterile and non-sterile) should be readily available but under strict access. As CoV2 carriers increased in our population in New Jersey, we treated each incoming trauma patient as a potentially CoV2-positive case and sought to reconfigure out trauma resuscitation area to minimize exposure of our supplies to aerosolized virus.